ISRAF DAN ETIKA LINGKUNGAN DALAM TREN THRIFTING: PERSPEKTIF EKOTEOLOGI ISLAM PADA SANTRIWATI URBAN - Afaf Sakinah Al Haddar; Rika Sartika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The thrifting phenomenon is growing rapidly among the younger generation as part of a lifestyle perceived as more economical and environmentally friendly. From a sustainable fashion perspective, the use of secondhand clothing is seen as reducing textile waste and supporting more sustainable consumption. However, on the other hand, the thrifting trend also has the potential to shift into consumer behavior if driven by a desire to follow fashion, thus contradicting the principle of israf (excess) in Islamic teachings. This study aims to analyze thrifting practices among urban female students (santriwati) through an Islamic ecotheological perspective by examining the relationship between the concept of israf, environmental ethics, and consumption behavior. This research used a qualitative approach with a phenomenological study design. Data were obtained through in-depth interviews with urban female students who actively thrift, observations of their consumption activities and social media use, and relevant documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and drawing and verifying conclusions. Data validity was tested through triangulation of sources and techniques. The results of this study indicate that female Islamic students (Islamic students) perceive thrifting not only as an alternative to obtaining affordable clothing but also as a form of environmental awareness through the reuse of fashion products. However, some informants demonstrated a tendency to overpurchase clothing due to social media trends, discounts, and the desire to follow certain clothing styles. This situation indicates a shift from sustainability-oriented consumption to israf behavior. The Islamic ecotheological perspective emphasizes that utilizing used goods can be a valuable practice of worship if it is based on the principles of simplicity (wasatiyyah), responsibility as a caliph on earth, and concern for environmental sustainability. This study emphasizes the importance of strengthening Islamic consumption ethics as part of ecological character education for female Islamic students in the digital culture era.